Impact of altered environment and early postnatal methamphetamine exposure on serotonin levels in the rat hippocampus during adolescence - Čechová, Barbora; Jurčovičová, Jana; Petríková, Ivana; Vaculín, Šimon; Šandera, Štěpán; Šlamberová, Romana (Laboratory animal research, 2024)
BACKGROUND: Methamphetamine (MA) is a highly abused psychostimulant across all age groups including pregnant women. Because developing brain is vulnerable by the action of drugs, or other noxious stimuli, the aim of our study was to examine the effect of early postnatal administration of MA alone or in combination with enriched environment (EE) and/or stress of separate housing, on the levels of serotonin (5HT) in the hippocampus of male rat pups at three stages of adolescence (postnatal day (PND) 28, 35 and 45). MA (5 mg/kg/ml) was administered subcutaneously (sc) to pups (direct administration), or via mothers' milk between PND1 and PND12 (indirect administration). Controls were exposed saline (SA). Pups were exposed to EE and/or to separation from the weaning till the end of the experiment. RESULTS: On PND 28, in sc-treated series, EE significantly increased the muted 5HT in SA pups after separation and restored the pronounced inhibition of 5HT by MA. No beneficial effect of EE was present in pups exposed to combination of MA and separation. 5HT development declined over time; EE, MA and separation had different effects on 5HT relative to adolescence stage. CONCLUSIONS: Present study shows that MA along with environment or housing affect 5HT levels, depending on both the age and the method of application (direct or indirect). These findings extend the knowledge on the effects of MA alone and in combination with different housing conditions on the developing brain and highlight the increased sensitivity to MA during the first few months after birth.
Keywords: Hippocampus; Methamphetamine; Adolescence; Serotonin; Enriched environment